Unemployment rate dynamics in small open economy: The case of Serbia - Anić, Aleksandra; Mladenovic, Zorica (Industrija, 2020)
Dynamic relationship among unemployment rate and key macroeconomic variables is explored for the Serbian economy that has been characterized by high unemployment rates since the outcome of the Great Recession. This analysis reveals how effective policy measures can be in reducing unemployment rate. Cointegrated vector autoregressive model is employed for period 2014-2019. Prior to multivariate dynamic modelling, the validity of hysteresis hypothesis for unemployment rate is assessed. Our results show significant negative long-run effect of real wages on unemployment rate, and positive long-run effect of real effective exchange rate appreciation on real wages. For further reduction of unemployment rate demand-side measures should be employed and real exchange rate depreciation should be avoided.